2019
DOI: 10.1186/s12936-019-2696-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the heterogeneity of human exposure to malaria vectors in an urban setting, Bouaké, Côte d’Ivoire, using an immuno-epidemiological biomarker

Abstract: BackgroundIn some African cities, urban malaria is a threat to the health and welfare of city dwellers. To improve the control of the disease, it is critical to identify neighbourhoods where the risk of malaria transmission is the highest. This study aims to evaluate the heterogeneity of malaria transmission risk in one city (Bouaké) in a West African country (Côte d’Ivoire) that presents several levels of urbanization.MethodsTwo cross-sectional studies were conducted in three neighbourhoods (Dar-es-Salam, Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
(31 reference statements)
5
22
2
Order By: Relevance
“…This data suggest the use of this specific antibody response to gSG6-P1 peptide as a pertinent marker to assess human exposure to Anopheles mosquitoes in Cameroon. This finding is similar to those reported in other regions in Africa [ 23 29 , 33 , 34 , 36 40 ], Americas [ 30 ] and Asia [ 31 , 32 ],where it was shown that the IgG response to the saliva peptide was associated to the level of exposure to mosquito bites [ 25 , 27 , 28 , 30 , 37 ] and to malaria infectious status [ 23 , 32 , 40 ]. Together, our data and from these previous studies confirm the relevance of this candidate biomarker to be used to assess human exposure to malaria vectors worldwide.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This data suggest the use of this specific antibody response to gSG6-P1 peptide as a pertinent marker to assess human exposure to Anopheles mosquitoes in Cameroon. This finding is similar to those reported in other regions in Africa [ 23 29 , 33 , 34 , 36 40 ], Americas [ 30 ] and Asia [ 31 , 32 ],where it was shown that the IgG response to the saliva peptide was associated to the level of exposure to mosquito bites [ 25 , 27 , 28 , 30 , 37 ] and to malaria infectious status [ 23 , 32 , 40 ]. Together, our data and from these previous studies confirm the relevance of this candidate biomarker to be used to assess human exposure to malaria vectors worldwide.…”
Section: Discussionsupporting
confidence: 90%
“…More specifically, IgG antibody response to the gSG6-P1 salivary peptide ( An . gambiae Salivary Gland Protein-6 peptide 1) has been validated as a relevant biomarker of Anopheles bites in various settings including West and East Africa [ 23 29 ], America [ 30 ] and Asia [ 31 , 32 ]. Moreover, in Africa, antibody response to gSG6-P1 salivary peptide was also found relevant for detecting human exposure to malaria vectors in the context of low and seasonal mosquito densities [ 24 , 26 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae Salivary Gland Protein-6 peptide 1) of An. gambiae saliva has been identified and validated as a pertinent biomarker of Anopheles bites [36][37][38]. It represents a proxy of human exposure to Anopheles bites and is a reliable tool for assessing spatial and temporal heterogeneity of exposure at the individual level [35].…”
mentioning
confidence: 99%
“…Furthermore, hot spots of Anopheles bite exposure inside neighborhoods were located in the northern part of GND and NDI and in the southern part of PSD. The presence of these hot spots could be explained by several individual and/or household factors, distance from breeding sites [43], and vegetation cover [44]. For instance, the particularly low dispersion of adult mosquitoes in urban areas could lead to high exposure among children living near Anopheles breeding sites, compared with exposure among those who live further away [36,45,46].…”
Section: Discussionmentioning
confidence: 99%